Fulfilling The Principles of Fairness and Equity in the Implementation of OECD Pillar One (Unified Approach) in Indonesia - Putro, Catur Anggoro; Rizal, Helmi; Mayangsari, Sekar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze how Indonesian tax regulations implement the OECD's Pillar One (Unified Approach) in terms of the principles of fairness and equity. The data collection techniques used in this research are literature studies and field research through interviews with key informants, namely people who are competent in understanding the problems discussed in this research. The research results show that the two-pillar design provides certainty of equality and justice in the international taxation framework in Indonesia. Pillar One is here to provide concessions that can be accepted by all parties actively involved and eliminate regulatory disharmony so that there is a common approach in overcoming the influence of the digital economy. The proposed Pillar 1 (Unified Approach) is an ideal level but is difficult to implement because there are so many challenges in it, Indonesia must minimize every obstacle that has been identified from the start to start implementing Pillar 1 and immediately align it with business processes at the Directorate General of Taxes related to reporting administration, law enforcement, supervision, and inspection. Indonesia must be able to adapt to the development of the digital economy in the world, especially regarding international tax regulations which have not been accommodated by the current regulations.